Alterations in amino acid metabolism during growth by Staphylococcus aureus following exposure to H2O2 – A multifactorial approach. Issue 5 (May 2018) - Murphy, Grace R.; Dunstan, R. Hugh; Macdonald, Margaret M.; Gottfries, Johan; Roberts, Tim K.
Abstract: Temperature and pH are known to vary in a wound site due to the immune response and subsequent healing processes. This study used a multifactorial design to examine the cellular responses of Staphylococcus aureus to hydrogen peroxide (0–100 mM) when bacteria were grown in temperatures of 37 ± 2 °C and pH 7 ± 1, conditions potentially encountered in wound sites. A centroid sample was included in the design which represented the mid-point values of all three environmental parameters (37 °C, pH 7, 50 mM H2 O2 ). Cytoplasmic extracts and corresponding medium supernatants were analysed for amino acid composition by gas chromatography. Exposures of S. aureus to H2 O2 during the inoculation process resulted in extended lag phases lasting well after the peroxide had been neutralised by the bacterium's antioxidant systems, after which the bacteria eventually resumed growth at equivalent rates to the controls. Even though the subsequent growth rates appeared normal, the cells exhibited a variant metabolic regime at the mid-exponential phase of growth as a result of the initial exposure to peroxide. The alterations in metabolism were reflected by the differential amino acid profiles measured in the cytoplasmic extracts (P < 0.0001). The data indicated that the metabolic responses to H2 O2 challenge were uniquely different depending on the variations of temperature and pH. The uptake patterns of amino acids from the media also altered depending on prevailing environmental conditions. From these results, it was proposed that a specific reproducible homeostasis could be induced under a specific set of defined environmental conditions. It was also evident that early toxic insults on the bacterial culture could have lasting impacts on cellular homeostasis after successive generations, even after the offending chemical had been removed and initial cell integrity restored. It was concluded that metabolic homeostasis would be continually adjusting and responding to changing environmental conditions to deploy defensive proteins as well as optimising processes for survival. The powerful ability to continually and rapidly adapt to the environment may represent the key feature supporting the virulence of S. aureus as an opportunistic pathogen invading the wound site.